An Introduction: Scapegoating the Jehovah’s Witnesses to Maintain the Cohesion of National Communities - Rigal-Cellard, Bernadette (The journal of CESNUR, 2020)
This and the next issue of The Journal of CESNURpresent papers from the September 3, 2020 seminar “Jehovah’s Witnesses and Their Opponents: Russia, the West, and Beyond,” which should have been held in Vilnius, Lithuania, on September 3, 2020, but was moved online because of the COVID-19 epidemic. Several papers focus on the reasons for the persecution of Jehovah’s Witnesses in Putin’s Russia. This introduction argues that René Girard’s theory of the scapegoat offers an additional explanation. In the present Russian context, the Jehovah’s Witnesses serve as the perfect scapegoat in Girardian sense.